2017
DOI: 10.3892/ijo.2017.4097
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin potentiates the antitumor effect of curcumin by inhibiting IKKβ/NF-κB/COX-2 signaling pathway

Abstract: Curcumin, a natural polyphenolic compound, has commonly been used as a food additive or in many traditional medicine remedies for over 2,000 years in many Asian countries. Melatonin is a hormone secreted from pineal glands of mammals and possesses diverse physiological functions. Both curcumin and melatonin have the effective potential to inhibit proliferation of various types of cancers, but there is no report on their combination for bladder cancer treatment, and the underlying mechanism remains poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Apart from NO, which has been extensively discussed above, some of these regulators are relevant to inflammation and to melatonin's anti‐inflammatory actions as well (Figure ). Melatonin has been shown many times to inhibit NF‐κB signaling and this had been convincingly related to the attenuation of inflammatory responses, under various experimental conditions . In particular, this effect was found to be decisive in the downregulation of two relevant proinflammatory factors, iNOS and COX‐2 (cyclooxygenase‐2) .…”
Section: Downstream Factors Of Melatonin's Actions With Relevance To mentioning
confidence: 93%
“…Apart from NO, which has been extensively discussed above, some of these regulators are relevant to inflammation and to melatonin's anti‐inflammatory actions as well (Figure ). Melatonin has been shown many times to inhibit NF‐κB signaling and this had been convincingly related to the attenuation of inflammatory responses, under various experimental conditions . In particular, this effect was found to be decisive in the downregulation of two relevant proinflammatory factors, iNOS and COX‐2 (cyclooxygenase‐2) .…”
Section: Downstream Factors Of Melatonin's Actions With Relevance To mentioning
confidence: 93%
“…Many studies have observed that melatonin treatment has beneficial effects on normal cells but induces apoptosis in tumor cells (70)(71)(72)(73)(74). Under melatonin treatment, large quantity of cytochrome C is released from the mitochondria into cytosol to induce apoptosis in tumor cells (75)(76)(77) while and the cytochrome C release is inhibited in the normal cells by melatonin (75,(78)(79)(80).…”
Section: Melatonin Metabolism In Mitochondriamentioning
confidence: 99%
“…Few studies have focused on the potential interaction of curcumin and melatonin in endometriosis. However, recent findings have shown that co-treatment of melatonin and curcumin can decrease COX-2 expression and can repress the NF-kappaB pathway [189]. Moreover, this combination can inhibit MMP-2, MMP-9 and TIMP-2 expression [189].…”
Section: Curcumin and Melatoninmentioning
confidence: 99%
“…However, recent findings have shown that co-treatment of melatonin and curcumin can decrease COX-2 expression and can repress the NF-kappaB pathway [189]. Moreover, this combination can inhibit MMP-2, MMP-9 and TIMP-2 expression [189]. Curcumin can activate sirtuin 1 (SIRT1) [134].…”
Section: Curcumin and Melatoninmentioning
confidence: 99%